2021
DOI: 10.1177/0956462421990218
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis in HIV-infected pregnant women in South Africa

Abstract: Background: Sexually transmitted infections (STIs) can be transmitted from mother to neonate. We determined the frequency of mother-to-child transmission (MTCT) of Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis to the newborn nasopharynx. Methods: This study was nested in a cohort study of etiologic testing versus syndromic management for STIs among pregnant women living with human immunodeficiency virus in South Africa. Mothers were tested for STIs using the GeneXpert platform within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Our results provide evidence that neonatal Chlamydia infections may be related to the rst phase of respiratory distress, according to Numazaki et al 37 and Sollecito et al 38 . This seems to contradict previous reports, since infection by C. trachomatis in newborns is generally reported at the end of the neonatal period or beyond and not in the rst day of life 7,39 . This suggests that proper management of infants in the rst hours of life is crucial.…”
Section: Discussioncontrasting
confidence: 86%
“…Our results provide evidence that neonatal Chlamydia infections may be related to the rst phase of respiratory distress, according to Numazaki et al 37 and Sollecito et al 38 . This seems to contradict previous reports, since infection by C. trachomatis in newborns is generally reported at the end of the neonatal period or beyond and not in the rst day of life 7,39 . This suggests that proper management of infants in the rst hours of life is crucial.…”
Section: Discussioncontrasting
confidence: 86%
“…These include adverse pregnancy outcomes (Silver et al., 2014) and increased transmission of viral infections as a result of damage to the epithelial layers of the reproductive tracts, including HIV (Kissinger & Adamski, 2013), HSV‐2 (Gottlieb et al., 2004; Kissinger, 2015), and HPV (Feng et al., 2018; Raffone et al., 2021), increasing the incidence of AIDS, genital herpes and cervical neoplasia, respectively. Vertical transmission during birth has also been documented (Peters et al., 2021). Although the infection is particularly ignored in men, as a result of its often‐asymptomatic nature, here too are severe long‐term risks, including diminished fertility, urethritis, prostatitis and, again, higher risk of HIV infection (Van Gerwen et al., 2021).…”
Section: Introductionmentioning
confidence: 98%
“…In their study they reported prevalence rates of 14.0% in South Africa; 6.0% in Uganda and 3.0% in Zimbabwe. 20 Other studies conducted in South African pregnant women have reported prevalence rates of 12.0% 21 ; 26.0% 1 and 36.8%. 22 However, these studies were conducted in HIV positive pregnant women which may account for some of the high prevalence rates.…”
Section: Discussionmentioning
confidence: 97%